Tops-Only Domains - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2011)
In this paper we consider the standard voting model with a finite set of alternatives A and n voters and address the following question: what are the characteristics of domains D" role="presentation">D that induce the property that every strategy-proof social choice function f:Dn→A" role="presentation">f:Dn→A satisfying unanimity, has the tops-only property? We first impose a minimal richness condition which ensures that for every alternative a, there exists an admissible ordering where a is maximal. We identify conditions on D" role="presentation">D that are sufficient for strategy-proofness and unanimity to imply tops onlyness in the general case of n voters and in the special case, n = 2. We provide an algorithm for constructing tops-only domains from connected graphs with elements of A as nodes. We provide several applications of our results. Finally, we relax the minimal richness assumption and partially extend our results.